Contextualizing comprehensive board diversity and firm financial performance: Integrating market, management and shareholderâs perspective - Hassan, R. (Cambridge University Press, 2018)
The study investigates demographic diversity, cognitive diversity and internal diversity within Islam among top-level management of firms and their impacts on the financial performance of Malaysian-listed companies. In addition, Muslim and non-Muslim women and Islamic religious diversity on corporate boards are investigated. Even though numerous organisations desire to be socially diverse, the significance of diversity for organisational performance remains uncertain. Are profitable companies inclined to improve board diversity or do other characteristics of the company contribute to firm performance? Does the participation of Muslim and non-Muslim women on corporate boards affect firm performance? Does internal diversity within Islam affect firm performance? Data from 330 Malaysian-listed companies in eleven full fledged sectors were used for the period from 2009 to 2013. This study employed econometrics methodology from panel data analysis to fill the research gap in the current management literature. This study used the interaction approach to examine empirically diverse corporate boards and their impacts on firm performance. This discussion included: (1) a combination of gender diversity and ethnic diversity and (2) a combination of gender diversity and foreign participation. The findings suggest that demographic, cognitive and internal diversity within Islam are significant predictors of a firmâs financial performance. Ethnic women on boards have a significant and negative impact on firm performance. Hence, companies having high profits are more accountable for encouraging diversity among top-level management. Copyright Â© Cambridge University Press and Australian and New Zealand Academy of Management 2018